Disaster Communication Based on Local Wisdom at Disaster Pried Areas - Hasmira, Mira Hasti (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Based on its location, Indonesia is very unique because it is prone to disasters. In disaster prevention and management efforts, disaster communication related to the government and communities in disaster-prone areas is required. To expedite the communication process that occurs, the government needs to increase knowledge and understanding of the local wisdom of the local community regarding the environment. This is important to increase public trust so that what is intended through disaster communication can be achieved.